The clinical method as a diagnosis method. A critique to a standing conception - Luis Alberto Corona Martínez (Medisur)
The importance of the clinical method in the assistance practice is out of question. In this article, through a systemic point of view and from the medical assistance perspective, it is analyzed how, historically conditioned, the clinical method has been considered up to this moment as a method for medical diagnosis, which limits the fulfillment of the general objective of the medical attention process. That’s why we consider the actual theory an insufficiently developed model for, as a teaching content in the Medicine career; contribute to the learning of the medical attention process.